The science of monotheism is viewed from the perspective of ontology, epistemology and axiology - Ramadani, Firman Ashar (Maliki Interdisciplinary Journal, 2025)
As a branch of science in Islam that discusses divinity, the science of monotheism has many rich aspects. From an ontological, epistemological, and axiological point of view, monotheism discusses the nature of God, His existence, and His relationship with the universe and humans. This perspective emphasizes the concept of the oneness of God (monotheism) as the main basis in the Islamic worldview. The science of monotheism epistemologically explains how humans gain knowledge about God through spiritual experience, revelation, and reason. In understanding faith, this approach distinguishes knowledge that is rational and intuitive. Meanwhile, the science of monotheism axiologically emphasizes the importance of applying divine values in daily life, which includes moral, social, and spiritual aspects. Therefore, this study shows that monotheism not only serves as the basis of faith, but also as a guideline for building a civilization that focuses on divine values. This research is expected to improve our understanding of the function of monotheism in human lif.